Technology integration to improve numeracy skills of dyscalculia students: Obstacles of inclusion schools in Indonesia - Suripah, Suripah; Zetriuslita, Zetriuslita; Sthephani, Aulia; Putri, Miranti Eka; Desvianti, Erika (Edelweiss Applied Science and Technology, 2024)
Several studies related to numeracy and technology have been carried out a lot, but researchers have not paid much attention to inclusion organizers in developing numeracy skills in dyscalculia-students by integrating technology. Therefore, this study aims to describe what obstacles are experienced by inclusion schools in developing the numeracy skills of technology-integrated dyscalculia students. This study is a qualitative study with a phenophysiological approach. The subjects of this study are 6 Headmasters and 12 teachers of inclusive schools in 6 junior high schools in Riau Province, Indonesia. Data was collected using interviews and Focus Group Discussion (FGD). Based on the results of data analysis, it can be concluded that there are several obstacles as follows: First, the limitation of human resources. Second, government policies and regulations have not presented comprehensive program guidelines. Third, the implementation of the curriculum in the learning process is inadequate. Fourth, the inclusive school culture is not conducive and some teachers are not used to integrating technology in mathematics learning for children with special needs. Fifth, the numeracy skills of dyscalculia students still has problems in calculation operations, and comprehension of mathematical symbols, and Sixth, the participation and support of the family have not been well communicated.